Synoptic Analysis of Effective Factors on Dust Frequency in West of Iran - Ali Mohammad Khorshiddoust; Gholam Hasan Mohammadi; Atefeh Hosseini Sadr; Khadijeh Javan; Abolfazl Jamali (نشریه جغرافیا و برنامه‌ریزی, 2014)
The effective synoptic systems on dust events was investigated in the west of Iran based on observed dusty days at 50 meteorological stations using principal component analysis (PCA) and geographical information system (GIS). Results showed that the first 5 components explained 69.11% of spatial variability of dust event variance. For detecting of affective synoptic systems, the computed correlation coefficient of stations with each component (Rotated Component Matrix) was transferred to the GIS environment, and synoptic patterns that affected spatial variability of dust events were simulated through Kriging interpolation method. It was shown that Azores high pressure system has the most effective role in frequency of days with dust in the west of Iran through the creation of surface thermal low pressures.